184k views
5 votes
Dy/dx = y/x , y(1) = −2

1 Answer

4 votes

Start with


(dy)/(dx)=(y)/(x)

Separate the variables:


(dy)/(y) = (dx)/(x)

Integrate both parts:


\displaystyle \int (dy)/(y) = \int(dx)/(x)

Which implies


\log(y) = \log(x)+c

Solving for y:


y = e^(\log(x)+c) = e^(\log(x))e^c=xe^c

Since
e^c is itself a constant, let's rename it
c_1.

Fix the additive constant imposing the condition:


y(1) = c_1\cdot 1 = -2\iff c_1=-2

So, the solution is


y(x) = -2x

User Rokia
by
5.8k points